Kedaulatan Allah dan Pandemi Covid-19: Sebuah Tinjauan Biblis-Teologis - James Lola; Donna Mutiara Junita Nainggolan (JURNAL LUXNOS, 2021)
Abstrac: This literature research traces the biblical-theological study of God's sovereignty related to the Pandemic. The problem of pandemic itself, in tracing the Bible, is more associated with infectious diseases especially pestilence, in which infectious diseases are given by God as a punishment for human sin, as a warning of a greater danger and also as God's way to save His chosen people. Keywords: Pandemic, God’s Sovereignity, Infectious Diseases, pestilence Abstrak: Penelitian kepustakaan ini menelusuri tentang kajian biblis-teologis tentang kedaulatan Allah berkaitan dengan Pandemic (penyakit menular). Persoalan pandemic sendiri, dalam penelusuran terhadap Alkitab lebih banyak dikaitkan dengan penyakit menular terutama penyakit sampar, di mana penyakit menular itu, diberikan oleh Allah sebagai penghukuman atas dosa manusia, sebagai peringatan akan bahaya yang lebih besar dan juga sebagai cara Allah untuk menyelamatkan umat pilihan-Nya.